2.9

From testwiki
Revision as of 15:29, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search
DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
2.9.E5 ρ 2 + f 0 ρ + g 0 = 0 superscript 𝜌 2 subscript 𝑓 0 𝜌 subscript 𝑔 0 0 {\displaystyle{\displaystyle\rho^{2}+f_{0}\rho+g_{0}=0}}
\rho^{2}+f_{0}\rho+g_{0} = 0

(rho)^(2)+ f[0]*rho + g[0] = 0
\[Rho]^(2)+ Subscript[f, 0]*\[Rho]+ Subscript[g, 0] == 0
Skipped - no semantic math Skipped - no semantic math - -
2.9.E6 α j = ( f 1 ρ j + g 1 ) / ( f 0 ρ j + 2 g 0 ) subscript 𝛼 𝑗 subscript 𝑓 1 subscript 𝜌 𝑗 subscript 𝑔 1 subscript 𝑓 0 subscript 𝜌 𝑗 2 subscript 𝑔 0 {\displaystyle{\displaystyle\alpha_{j}=(f_{1}\rho_{j}+g_{1})/(f_{0}\rho_{j}+2g% _{0})}}
\alpha_{j} = (f_{1}\rho_{j}+g_{1})/(f_{0}\rho_{j}+2g_{0})

alpha[j] = (f[1]*rho[j]+ g[1])/(f[0]*rho[j]+ 2*g[0])
Subscript[\[Alpha], j] == (Subscript[f, 1]*Subscript[\[Rho], j]+ Subscript[g, 1])/(Subscript[f, 0]*Subscript[\[Rho], j]+ 2*Subscript[g, 0])
Skipped - no semantic math Skipped - no semantic math - -
2.9.E7 ρ j ( f 0 + 2 ρ j ) s a s , j = r = 1 s ( ρ j 2 2 r + 1 ( α j + r - s r + 1 ) + ρ j q = 0 r + 1 ( α j + r - s r + 1 - q ) f q + g r + 1 ) a s - r , j subscript 𝜌 𝑗 subscript 𝑓 0 2 subscript 𝜌 𝑗 𝑠 subscript 𝑎 𝑠 𝑗 superscript subscript 𝑟 1 𝑠 superscript subscript 𝜌 𝑗 2 superscript 2 𝑟 1 binomial subscript 𝛼 𝑗 𝑟 𝑠 𝑟 1 subscript 𝜌 𝑗 superscript subscript 𝑞 0 𝑟 1 binomial subscript 𝛼 𝑗 𝑟 𝑠 𝑟 1 𝑞 subscript 𝑓 𝑞 subscript 𝑔 𝑟 1 subscript 𝑎 𝑠 𝑟 𝑗 {\displaystyle{\displaystyle\rho_{j}(f_{0}+2\rho_{j})sa_{s,j}=\sum_{r=1}^{s}% \left(\rho_{j}^{2}2^{r+1}\genfrac{(}{)}{0.0pt}{}{\alpha_{j}+r-s}{r+1}+\rho_{j}% \sum_{q=0}^{r+1}\genfrac{(}{)}{0.0pt}{}{\alpha_{j}+r-s}{r+1-q}f_{q}+g_{r+1}% \right)a_{s-r,j}}}
\rho_{j}(f_{0}+2\rho_{j})sa_{s,j} = \sum_{r=1}^{s}\left(\rho_{j}^{2}2^{r+1}\binom{\alpha_{j}+r-s}{r+1}+\rho_{j}\sum_{q=0}^{r+1}\binom{\alpha_{j}+r-s}{r+1-q}f_{q}+g_{r+1}\right)a_{s-r,j}

rho[j]*(f[0]+ 2*rho[j])*s*a[s , j] = sum(((rho[j])^(2)*(2)^(r + 1)*binomial(alpha[j]+ r - s,r + 1)+ rho[j]*sum(binomial(alpha[j]+ r - s,r + 1 - q)*f[q], q = 0..r + 1)+ g[r + 1])*a[s - r , j], r = 1..s)
Subscript[\[Rho], j]*(Subscript[f, 0]+ 2*Subscript[\[Rho], j])*s*Subscript[a, s , j] == Sum[((Subscript[\[Rho], j])^(2)*(2)^(r + 1)*Binomial[Subscript[\[Alpha], j]+ r - s,r + 1]+ Subscript[\[Rho], j]*Sum[Binomial[Subscript[\[Alpha], j]+ r - s,r + 1 - q]*Subscript[f, q], {q, 0, r + 1}, GenerateConditions->None]+ Subscript[g, r + 1])*Subscript[a, s - r , j], {r, 1, s}, GenerateConditions->None]
Failure Failure Error
Failed [1 / 1]
2.9.E10 g 0 κ = 2 f 0 f 1 - 4 g 1 subscript 𝑔 0 𝜅 2 subscript 𝑓 0 subscript 𝑓 1 4 subscript 𝑔 1 {\displaystyle{\displaystyle\sqrt{g_{0}}\kappa=\sqrt{2f_{0}f_{1}-4g_{1}}}}
\sqrt{g_{0}}\kappa = \sqrt{2f_{0}f_{1}-4g_{1}}
4 g 0 α = g 0 + 2 g 1 4 subscript 𝑔 0 𝛼 subscript 𝑔 0 2 subscript 𝑔 1 {\displaystyle{\displaystyle 4g_{0}\alpha=g_{0}+2g_{1}}}
sqrt(g[0])*kappa = sqrt(2*f[0]*f[1]- 4*g[1])
Sqrt[Subscript[g, 0]]*\[Kappa] == Sqrt[2*Subscript[f, 0]*Subscript[f, 1]- 4*Subscript[g, 1]]
Skipped - no semantic math Skipped - no semantic math - -
2.9.E11 2 g 0 α 2 - ( f 0 f 1 + 2 g 0 ) α + 2 g 2 - f 0 f 2 = 0 2 subscript 𝑔 0 superscript 𝛼 2 subscript 𝑓 0 subscript 𝑓 1 2 subscript 𝑔 0 𝛼 2 subscript 𝑔 2 subscript 𝑓 0 subscript 𝑓 2 0 {\displaystyle{\displaystyle 2g_{0}\alpha^{2}-(f_{0}f_{1}+2g_{0})\alpha+2g_{2}% -f_{0}f_{2}=0}}
2g_{0}\alpha^{2}-(f_{0}f_{1}+2g_{0})\alpha+2g_{2}-f_{0}f_{2} = 0

2*g[0]*(alpha)^(2)-(f[0]*f[1]+ 2*g[0])*alpha + 2*g[2]- f[0]*f[2] = 0
2*Subscript[g, 0]*\[Alpha]^(2)-(Subscript[f, 0]*Subscript[f, 1]+ 2*Subscript[g, 0])*\[Alpha]+ 2*Subscript[g, 2]- Subscript[f, 0]*Subscript[f, 2] == 0
Skipped - no semantic math Skipped - no semantic math - -